2013
DOI: 10.1038/clpt.2013.165
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Regulatory Features of Drugs Not Initially Approved by the FDA

Abstract: US Food and Drug Administration (FDA) denials of New Drug Applications (NDAs) are often controversial, yet little is known about the basis and characteristics of these decisions. We reviewed new drugs and biologics evaluated by FDA advisory committees between 2007 and 2009 and found that half (27/52, 52%) were unapproved in the first cycle. By 2013, 63% had been approved. Products with initial safety concerns (62%) were much more likely to be approved eventually than drugs with efficacy concerns (8%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…From 2001 to 2009, five articles were published [4][5][6][7][8]. Interest in the topic continued to increase, with six relevant articles being published from 2010 to 2012 [9][10][11][12][13][14] and 12 articles appearing from 2013 to 2015 [15][16][17][18][19][20][21][22][23][24][25][26]. The timeframe for which data were analysed in the studies ranged from 1981 to 2014.…”
Section: Observations Publication Characteristicsmentioning
confidence: 99%
“…From 2001 to 2009, five articles were published [4][5][6][7][8]. Interest in the topic continued to increase, with six relevant articles being published from 2010 to 2012 [9][10][11][12][13][14] and 12 articles appearing from 2013 to 2015 [15][16][17][18][19][20][21][22][23][24][25][26]. The timeframe for which data were analysed in the studies ranged from 1981 to 2014.…”
Section: Observations Publication Characteristicsmentioning
confidence: 99%
“…From a drug development perspective, DILI caused a number of regulatory actions in the past decades. Very recently, Wang et al [4] reviewed formal reasons for non-approval of 27 drug applications and identified hepatotoxicity in 4 (15%) cases. The oral anticoagulant ximelgatran is a typical example of interruption of drug development for hepatic concern: in 2006, the manufacturer withdrew a pending application to the Food and Drug Administration (FDA).…”
Section: Field Of Interestmentioning
confidence: 99%